INTERAKSI SOSIAL NELAYAN PURSE SEINE DI NEGERI YAINUELO KABUPATEN MALUKU TENGAH - Pical, Venda Jolanda; Anaktototy, Jofita (PAPALELE (Jurnal Penelitian Sosial Ekonomi Perikanan dan Kelautan), 2024)
This study analyzes the associative social interactions of purse seine fishermen in Yainuelo Village, Amahai District, Central Maluku Regency. This area is rich in fishery resources, with most residents relying on fishing as their primary source of livelihood. Social interactions between fishermen and traders play a crucial role in utilizing marine resources, building solidarity, and enhancing operational efficiency. The research employs a descriptive qualitative method, gathering primary data through interviews, observations, and documentation, alongside secondary data from official sources. The findings reveal various forms of cooperation among fishermen, including the determination of fishing locations and the hauling of nets. These social interactions are categorized into four types: individual-to-individual (I-I), individual-to-group (I-G), group-to-individual (G-I), and group-to-group (G-G). Each interaction type demonstrates unique social dynamics that reinforce solidarity and work efficiency. This study recommends enhancing cooperation among fishermen and providing support to strengthen existing social networks, aimed at optimizing fishery yields and improving the welfare of the local community.